Evidence for wind patterns and associated landscape response in Western Europe between 46 and 16 ka cal. BP. (15th December 2022) - Kämpf, Lucas; Rius, Damien; Duprat-Oualid, Fanny; Crouzet, Christian; Millet, Laurent
Abstract: During the last glacial period, the North Atlantic region experienced pronounced, millennial-scale alternations in climate characterized by cold stadial and milder interstadial conditions. These rapid climatic changes are recorded in Greenland ice cores and various terrestrial proxy records of Europe. Nonetheless, the scarcity and age uncertainties associated with records north of the Alps have long hindered our understanding of continental-scale climate impacts and associated environmental responses. Here we present high-resolution geochemical records from Bergsee Lake (SW Germany) to probe centennial changes in aeolian and organic matter fluxes between 46 and 16 ka cal. BP. We compare and combine these data with a pollen-based vegetation reconstruction. Abrupt decreases in dust influx were followed by tree expansions during Greenland interstadials 11 to 2. A further five interstadial-like warming phases are recorded between 31 and 16 ka cal. BP. These warming phases are not recorded in Greenland but rather relate to European-scale shifts in atmospheric circulation patterns. We find that the wind activity varies on a persistent period of 2400–3100 years that probably reflects a dominant solar forcing on the glacial climate of Europe. Highlights: Records of Last Glacial abrupt climate changes are still scarce north of the Alps. We present high-resolution geochemical record from Bergsee Lake (SW Germany). Decreases in dust influx were followed by tree expansions during GI-11 to 2. A further five interstadial-like warming phases recorded between 31 and 16 ka cal. BP.